2010
DOI: 10.1029/2010gl045269
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated perchlorate at the Mars Phoenix landing site: Evidence for thin film liquid water on Mars

Abstract: NASA's Phoenix mission, which landed on the northern plains of Mars in 2008, returned evidence of the perchlorate anion distributed evenly throughout the soil column at the landing site. Here, we use spectral data from Phoenix's Surface Stereo Imager to map the distribution of perchlorate salts at the Phoenix landing site, and find that perchlorate salt has been locally concentrated into subsurface patches, similar to salt patches that result from aqueous dissolution and redistribution on Earth. We propose tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 24 publications
(37 reference statements)
3
87
0
Order By: Relevance
“…The accuracy of model predictions in these studies relies upon two key assumptions: (1) liquid water is present to mediate precipitation/dissolution reactions and (2) equilibrium salt assemblages form, as opposed to metastable assemblages. These assumptions are reasonable for the Phoenix site given that there are multiple lines of evidence suggesting liquid water has been active at the Phoenix site Rennó et al, 2009;Cull et al, 2010;Stillman and Grimm, 2011;Fisher et al, 2014). Furthermore, the $600 Ma age of the soil suggests that there has been sufficient time for brines and salts to equilibrate.…”
Section: Application To the Rosy Red Soil Solutions Measured By The Pmentioning
confidence: 94%
See 1 more Smart Citation
“…The accuracy of model predictions in these studies relies upon two key assumptions: (1) liquid water is present to mediate precipitation/dissolution reactions and (2) equilibrium salt assemblages form, as opposed to metastable assemblages. These assumptions are reasonable for the Phoenix site given that there are multiple lines of evidence suggesting liquid water has been active at the Phoenix site Rennó et al, 2009;Cull et al, 2010;Stillman and Grimm, 2011;Fisher et al, 2014). Furthermore, the $600 Ma age of the soil suggests that there has been sufficient time for brines and salts to equilibrate.…”
Section: Application To the Rosy Red Soil Solutions Measured By The Pmentioning
confidence: 94%
“…Evidence for past liquid water includes a relatively high abundance of carbonate ) and spectrally-inferred patches of perchlorate that were likely distributed by aqueous processes (Cull et al, 2010(Cull et al, , 2014. Starting from an initial WCL type solution, equilibrium models have been used to predict salt assemblages that form during either freezing or evaporation (Hanley et al, 2012;Marion et al, 2010;Toner et al, 2014bToner et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The Surface Stereo Imager on Phoenix also identified spectral features consistent with hydrated perchlorate in the excavated trenches, suggesting that aqueous redistribution of perchlorates had likely occurred [Cull et al, 2010]. Recent reanalysis of the Phoenix WCL data indicated that magnesium perchlorate hexahydrate Mg(ClO 4 ) 2 · 6H 2 O is the most probable parent salt found at that site [Toner et al, 2014a].…”
Section: Introductionmentioning
confidence: 99%
“…Another result from Phoenix was the detection of perchlorate salts. The mapping of the distribution of perchlorate salts has been explained with the presence of thin films of liquid water which are responsible for translocating perchlorates from the surface to the sub-surface (Cull et al 2010), bringing into question their role in slope processes.…”
Section: Volatile-rich Processes and Transient Meltingmentioning
confidence: 99%